Demonstrating the high Voc potential of PEDOT:PSS/c-Si heterojunctions on solar cells. (September 2017) - Gogolin, Ralf; Zielke, Dimitri; Descoeudres, Antoine; Despeisse, Matthieu; Ballif, Christophe; Schmidt, Jan
Abstract: In this study, we demonstrate the high surface passivation quality of PEDOT:PSS/c-Si junctions for the first time on solar cell level, reaching a record high Voc value of 688 mV after full-area metallization of the PEDOT:PSS. We achieve this by combining the PEDOT:PSS hole-selective layer at the rear of the crystalline silicon wafer with a well-passivating electron-selective a-Si:H(i/n) layer stack at the front. Our results clearly prove the excellent hole selectivity of PEDOT:PSS on crystalline silicon.